Factors Affecting Student Financial Literacy - Leni Triana; Ibrohim Ibrohim (Yayasan Ilomata, 2022)
Students, on the whole, have more leeway to exercise their own discretion regarding matters of personal finance. On the other hand, the current phenomenon does not indicate that students have a good grasp of financial concepts. In order for students to be able to make the most of the money they have, they need to be provided with an education that teaches them financial information and skills and teaches them how to properly handle funds. The goal of this study is to determine which factors, if any, have an effect on the financial literacy level possessed by university students in the city of Serang, Indonesia. The method used in this research is to go directly to the respondents who are the samples in the study to get primary data. The sampling technique in this study ses a proportionate random sampling with data collection techniques using a questionnaire distribution technique. Factor analysis of 17 indicator variables resulted in 5 forming factors, namely: 1) Management Factors, 2) Income Factors, 3) Budgeting Factors, 4) Education Factors, and 5) Planning Factors.